THE APPLICABILITY OF THE ECLECTIC METHOD ON THE DEVELOPMENT OF THE ORAL PRODUCTION - Mayra Alejandra Marcillo; Galo Alejandro Palacios (Journal of English Education, 2017)
Developing our students’ English oral expression in Public Institutions is a process that needs to be carefully analyzed by teachers. It is more than selected a method, it is more than following step by step what a theory says. It is going beyond our students’ needs. It is a deeply study of what a student really can do and needs to learn. Based on a post-method pedagogy which provides teachers the ability to break down barriers to the imposition of a specific method and make the teaching process more effective, this paper proposes the application of the eclectic method for the development of the oral expression of public high school students encouraging teachers to see the teaching process from a different and modern perspective. By analyzing the principles and features of this method, this paper describes the research made on a Public Institution with students in third year. With the goal of improving each one of the principal components of the English oral expression: range, accuracy, fluency, pronunciation and coherence, there were used selected methods, techniques and strategies based upon the students’ learning styles and needs. The observation and Interview techniques were used on data collection and the parameters of Inferential and descriptive statistic were applied in order to analyze the results achieved. They showed that even though not all of the group of the students could achieve the B1 level in reference to the Common European Framework and required by the Ministry of Education, a large number of them were able to increase their English oral expression. According to this data, this paper concludes that the selection of objectives, the modern teacher‘s and student’s role, the use of different but selected methods, the linguistic input activation and the contextualization had a significant impact on learners´ learning.